Um olhar sobre a interdisciplinaridade no ensino superior: um estudo de caso no Bacharelado Interdisciplinar em Ciência e Tecnologia da Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Due to the need to overcome the fragmentation of scientific knowledge, interdisciplinarity emerged in the second half of the last century. This project aimed to know the advances in the perception of students and teachers linked to the Interdisciplinary Bachelor of Science and Technology (BICT), from the Federal University of Pampa (UNIPAMPA), about interdisciplinarity and its importance in the training of a researcher. For this, we used a qualitative and quantitative research, using a set of data obtained in bibliographic research and through a questionnaire with the students and professors linked to the BICT of UNIPAMPA and graduates trained in the course; the Pedagogical Course Project - PPC in force was used as a research instrument. The responses revealed teaching experiences in the university context under an interdisciplinary character; the perceptions and difficulties are raised, visualized in the comprehension of the investigated subjects; this material obtained is compared with the Political Course Project - PPC and with the concepts extracted from the bibliographic review. It appears that interdisciplinarity is more thought and spoken than experienced. Bearing in mind the importance of interdisciplinarity in the training of future bachelors, professionals and researchers in the area of science and technology, we seek to visualize how the distance between the spoken, the thought and the effectively practiced in the academic scope can be reduced.
Keywords: Interdisciplinaridade; Ensino superior; Educação; Interdisciplinarity; University education; Education; CNPQ::CIENCIAS EXATAS E DA TERRA